NATURAL MEDIA FOR THE GROWTH OF CANDIDA ALBICANS CAUSES OF CANDIDIASIS BY ARTOCARPUS COMMUNIS - Yunan Jiwintarum; Urip Urip; Anas Fadli Wijaya; Maruni Wiwin Diarti (poltekkes kemenkes mataram, 2017)
a candida albicans requires a source of nutrients especially carbohydrates that are sufficient for its growth. Semi-synthesis media is the most common medium for growing Candida albicans. Semi-synthesized media composes of natural and synthesis materials. An abundance of biological sources in nature with higher carbohydrate content than natural ingredients on semi-synthesized media encourage to find the materials of alternative media from different carbohydrate sources, particularly grains, one of them is breadnut seed. This study aimed to find out a potential of Artocarpus communis as an alternative media for the growth of Candida albicans causes of candidiasis. This study was true experiment, used 6 replications and 4 treatments with PDA as control media, the media of Artocarpus communis with concentration of 10%, 20%, and 30%. The data of Candida albicans growth was tested statistically used One Way Anova with 95% confidence level or α = 0.05. The result indicated that a number of Candida albicans growth on PDA media was 13.7 colonies, on alternative media of Artocarpus communis with the concentration of 10% was an average of 13.5 colonies, the concentration of 20% was an average of 16.3 colonies and the concentration of 30% was an average of 24 colonies. The conclusion: the Artocarpus communis can be employed as an alternative natural media of Candida albicans growth.